Spatial heterogeneity of climate variation and vegetation response for Arctic and high-elevation regions from 2001–2018. (14th January 2020) - Wu, Wenjin; Sun, Xiaohui; Epstein, Howard; Xu, Xiyan; Li, Xinwu
Abstract: In recent decades, an amplification of warming in Arctic and high-elevation regions has been widely observed, along with a general enhancement of vegetation growth. However, driven by variability in controlling factors and complex mechanisms, climate and vegetation changes can be highly heterogeneous in space and time. In this study, an analysis is performed separating Arctic and Tibetan Plateau (TP) vegetated areas into various units according to a map of terrestrial ecoregions. The most recent variations of heat, moisture, and vegetation growth (MODIS Normalized Difference Vegetation Index) are evaluated over 2001–2018. Relationships among the climate and vegetation variables are assessed. Six distinct change patterns are identified: (1) synchronized increase of day and night temperature and precipitation during April to October coinciding with strong vegetation greening, (2) profound warming with no change in precipitation and vegetation, (3) an increase of summer temperature and vegetation with a negative latitudinal gradient, (4) greening under increased precipitation without warming, (5) browning not likely being driven by climate, (6) warming only during the nighttime and moderately enhanced vegetation growth. It is demonstrated that vegetation growth in the Arctic and TP is largely controlled by nighttime temperature and precipitation, as opposed to daytime temperature. The exception is the Canadian Arctic, where greening is directly related to summer daytime warming, and a contrasting relationship is observed on the TP. The underlying causes of these patterns are discussed, relating them to multiple mechanisms reported in the literature. These findings may help to further understand the changing Arctic and high-elevation climate and its effects on vegetation growth.